Introduction to the modelling of marine ecosystems - Fennel, W. (Wolfgang); Neumann, T. (Thomas) (Amsterdam : Elsevier Science, 2014)
Introduction to the Modelling of Marine Ecosystems, Second Edition provides foundational information on the construction of chemical and biological models - from simple cases to more complex biogeochemical models and life cycle resolving model components. This step-by-step approach to increasing the complexity of the models allows readers to explore the theoretical framework and become familiar with the models even when they have limited experience in mathematical modeling. Introduction to the Modelling of Marine Ecosystems shows how biological model components can be integrated into three dim.
5.3.3 Turbulent Diffusion in Collinear Flows5.3.3.1 Turbulent Diffusion in a Shear Flow; 5.3.3.2 Turbulent Diffusion in Eddies; 5.3.3.3 Turbulent Diffusion in Deformation Fields; 5.3.3.4 Aggregation at Convergence Lines; 5.3.4 Patchiness and Critical Scales; 5.4 Upscaling and Downscaling; 5.5 Resolution of Processes; 5.5.1 State Densities and Their Dynamics; 5.5.2 Primary Production Operator; 5.5.3 Predator-Prey Interaction; 5.5.4 Mortality Operators; 5.5.5 Model Classes; Chapter 6: Coupled Models; 6.1 Introduction; 6.2 Regional to Global Models; 6.3 Circulation Models; 6.4 Baltic Sea.
Print version record.
Includes bibliographical references and index.
English.
Keywords: Biotic communities -- Mathematical models; Marine ecology; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; Biotic communities -- Mathematical models; Marine ecology; Electronic books